Peningkatan Keterampilan Membaca Nyaring Melalui Metode Latihan Terbimbing Pada Siswa Kelas 2 Sdn 24 Palu - masita, Masita; Rizal, Rizal; Surahman, Surahman; Aqil, Muhammad (JURNAL DIKDAS, 2022)
The objective of this study was to ascertain whether the guided practice method could enhance the competencies of second grade students at SDN 24 Palu. The objective is to enhance the reading aloud abilities of grade 2 students at SDN 24 Palu through the utilisation of the guided practice method, thereby enabling them to read with proficient and accurate pronunciation and intonation. This research is a classroom action research project, employing a research design based on the Kurt Lewin model of PTK, which encompasses the following four phases: planning, action, observation, and reflection. The assessment was based on the observation of the reading aloud process. The subjects were 25 second-grade students from SDN 24 Palu. The action research process was conducted in two cycles. The data was collected in the form of a table of reading aloud skills, and based on this data, the researchers were able to determine the assessment of the reading aloud skill process. The aforementioned table of learning outcomes for grade 2 students at SDN 24 Palu was consulted. The results demonstrated that the initial observation yielded an average learning outcome of 60.96, with only 20% of the learning process deemed complete. The implementation of the guided practice method in Cycle 1 led to an increase in the average result for reading aloud skills to 76. The average learning outcome was 68.68 with a percentage of completeness of 60%. This reflected the results of the first cycle, whereby it was possible to increase the average student learning outcome in the second cycle to 87.68 with a percentage of completeness reaching 88%. Based on these results, it can be concluded that the guided practice method can improve the ability to read aloud.